2012 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2012
DOI: 10.1109/icassp.2012.6287822
|View full text |Cite
|
Sign up to set email alerts
|

Musical genre classification using melody features extracted from polyphonic music signals

Abstract: We present a new method for musical genre classification based on high-level melodic features that are extracted directly from the audio signal of polyphonic music. The features are obtained through the automatic characterisation of pitch contours describing the predominant melodic line, extracted using a state-of-the-art audio melody extraction algorithm. Using standard machine learning algorithms the melodic features are used to classify excerpts into five different musical genres. We obtain a classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 7 publications
(9 reference statements)
0
23
0
Order By: Relevance
“…For Classify, most works measure MGR performance by classification accuracy (the ratio of "correct" predictions to all observations) computed from k-fold stratified cross-validation (kfCV), e.g., 2fCV (4 papers) [7,22,23,56], 3fCV (3 papers) [18,71,74], 5fCV (6 papers) [3,13,30,31,53,100], and 10fCV (55 papers) [2,5,9,11,14,16,17,24-26,28,29,34,35,37,39-42, 44,47-51,57,58,60-64,66-68,70,72,73,75,76,78,79,82-85,88-91,94-96,98,99]. Most of these use a single run of cross-validation; however, some perform multiple runs, e.g., 10 independent runs of 2fCV (10x2CV) [56] or 20x2fCV [22,23], 10x3fCV [71,74], and 10x10fCV [37,70,72,75,[83][84][85]. In one experiment, Li and Sleep [42] use 10fCV with random partitions; but in another, they partition the excerpts into folds based on their file number -roughly implementing an artist filter.…”
Section: Using Gtzanmentioning
confidence: 99%
“…For Classify, most works measure MGR performance by classification accuracy (the ratio of "correct" predictions to all observations) computed from k-fold stratified cross-validation (kfCV), e.g., 2fCV (4 papers) [7,22,23,56], 3fCV (3 papers) [18,71,74], 5fCV (6 papers) [3,13,30,31,53,100], and 10fCV (55 papers) [2,5,9,11,14,16,17,24-26,28,29,34,35,37,39-42, 44,47-51,57,58,60-64,66-68,70,72,73,75,76,78,79,82-85,88-91,94-96,98,99]. Most of these use a single run of cross-validation; however, some perform multiple runs, e.g., 10 independent runs of 2fCV (10x2CV) [56] or 20x2fCV [22,23], 10x3fCV [71,74], and 10x10fCV [37,70,72,75,[83][84][85]. In one experiment, Li and Sleep [42] use 10fCV with random partitions; but in another, they partition the excerpts into folds based on their file number -roughly implementing an artist filter.…”
Section: Using Gtzanmentioning
confidence: 99%
“…Salomon et al [30] combined MFCC with melodic highlevel features that describe the pitch contour of the main melody in polyphonic music recordings. The authors reported a classification accuracy of 82 % for five music genres.…”
Section: Related Workmentioning
confidence: 99%
“…They used the log energies and Mel-frequency cepstrum coefficients as the musical feature, and used support vector machine as a classifier. J. Salamon [13] et. al.…”
Section: Related Workmentioning
confidence: 99%